Utilization of Jumbo animated movie as a medium for moral learning - Arjuna, Arjuna; Ulhaq, Muhammad Miftah; Ariska, Mutiara; Harahap, Yasmin; Maslani, Maslani (Jurnal Iman dan Spiritualitas, 2025)
This study explores the use of animated films as a medium for internalizing moral values in Islamic elementary schools, specifically focusing on the implementation of the animated film Jumbo at MIS Al-Huda Haurwangi, Cianjur. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings reveal that although the film was shown only once, it effectively engaged students and facilitated their understanding of moral values such as honesty, responsibility, politeness, and cooperation. Students demonstrated enthusiasm during the screening and were able to identify moral lessons through guided discussions led by the teacher. However, the study also highlights challenges, including limited technological infrastructure and the dependence on the teacher’s ability to facilitate reflection. Despite its single-session implementation, the animated film proved to be a promising alternative for moral education, particularly for younger students who benefit from concrete visual examples. The research recommends enhancing multimedia facilities in madrasahs and providing teacher training to maximize the potential of digital media in character education. This study contributes to the growing body of literature on innovative pedagogical tools in Islamic education and underscores the importance of contextualizing digital media within traditional learning frameworks.